2016
DOI: 10.1016/j.fct.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing infant exposure to persistent organic pollutants via dietary intake in Australia

Abstract: Persistent organic pollutants (POPs) including polybrominated diphenyl ethers (PBDEs); organochlorine pesticides (OCPs); and polychlorinated biphenyls (PCBs) persist in the environment, bioaccumulate, and pose a risk of causing adverse human health effects. Typically, exposure assessments undertaken by modeling existing intake data underestimate the concentrations of these chemicals in infants. This study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Once produced, these chemicals remain in our ecosystem for several years and continue to exert their harmful effect on human health in the form of diseases like cancer, birth defects, and neurological and immunological disorders (El-Shahawi et al 2010 ). Certain POPs are associated with immunodeficiency in infants, while a few others are substantial risk factors for breast cancer (Toms et al 2016 ; Mouly and Toms 2016 ). Brain development in infants may get affected due to exposure to POPs, as it has been shown that children exposed to POPs during infancy scored comparatively lower in intelligence and concentration measurements (Tran and Miyake 2017 ).…”
Section: Air Pollution: An Overviewmentioning
confidence: 99%
“…Once produced, these chemicals remain in our ecosystem for several years and continue to exert their harmful effect on human health in the form of diseases like cancer, birth defects, and neurological and immunological disorders (El-Shahawi et al 2010 ). Certain POPs are associated with immunodeficiency in infants, while a few others are substantial risk factors for breast cancer (Toms et al 2016 ; Mouly and Toms 2016 ). Brain development in infants may get affected due to exposure to POPs, as it has been shown that children exposed to POPs during infancy scored comparatively lower in intelligence and concentration measurements (Tran and Miyake 2017 ).…”
Section: Air Pollution: An Overviewmentioning
confidence: 99%
“…While comparisons must be made with caution due to small sample sizes and different geographical locations, this does indicate a 10 fold decrease for BDE-47 in household dust which may influence exposure via indoor environments. Assessment of PBDEs in baby foods in Australia in 2015 suggests a decrease in concentration from a previous time point of 2004 but again, comparisons must be made with caution due to small sample sizes (Toms et al 2016). Children born in the most recent time periods appear to have lower environmental exposures than those born early in the monitoring period.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 41 targeted compounds, 19 compounds were detected in at least one of the 46 samples (LOQ; 0.005 to 0.02 ng/g-w.w.) (Table 2, Table S2). HCB was most frequently detected (78%), followed by p,p'-DDE (65%), and TC (57%) ( Some reports have discussed the dietary intakes of organohalogenated compounds in baby food from the US and China (Liu et al, 2014), Australia (Toms et al, 2016), Korea (Jeong et al, 2014a;Jeong et al, 2014b) and Spain (Lorán et al, 2010). These studies were not based on 24-h duplicate-diet, but rather on an individual ingredient or commercial-, homemade-baby food.…”
Section: Organohalogenated Compounds In 24-h Baby Duplicate Dietmentioning
confidence: 99%